2020
DOI: 10.3390/ijerph17041191
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers in Dysmenorrhea and Therapeutic Options

Abstract: Dysmenorrhea often significantly reduces the quality of women’s life and is still an important public health problem. Despite numerous studies, the pathomechanism of dysmenorrhea is not fully understood. Previous research indicates the complexity of biochemical reactions between the endocrine, vascular, and immune systems. Prostaglandins play a major role in the pathomechanism of dysmenorrhea. In contrast, cytokines and other proinflammatory factors in primary dysmenorrhea are less studied. In addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
137
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 90 publications
(177 reference statements)
1
137
0
16
Order By: Relevance
“…Two years later, it has been suggested that inflammation and endothelial dysfunction may be characterized by lipid peroxidation [ 25 ]. Nowadays, one of the convincing mechanisms that stand behind elevated markers of inflammation is based on the role of progesterone in the menstrual cycle [ 8 , 16 ] ( Figure 2 ). During the first half of secretory (luteal) phase in the menstrual cycle, the level of progesterone increases, which has anti-inflammatory and regulating (prostaglandins and leukocytes synthesis) effects on endometrial tissue [ 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two years later, it has been suggested that inflammation and endothelial dysfunction may be characterized by lipid peroxidation [ 25 ]. Nowadays, one of the convincing mechanisms that stand behind elevated markers of inflammation is based on the role of progesterone in the menstrual cycle [ 8 , 16 ] ( Figure 2 ). During the first half of secretory (luteal) phase in the menstrual cycle, the level of progesterone increases, which has anti-inflammatory and regulating (prostaglandins and leukocytes synthesis) effects on endometrial tissue [ 8 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, one of the convincing mechanisms that stand behind elevated markers of inflammation is based on the role of progesterone in the menstrual cycle [ 8 , 16 ] ( Figure 2 ). During the first half of secretory (luteal) phase in the menstrual cycle, the level of progesterone increases, which has anti-inflammatory and regulating (prostaglandins and leukocytes synthesis) effects on endometrial tissue [ 8 , 16 ]. In the second half of the luteal phase, the progesterone level begins to fall, which causes the secretion of arachidonic acid and its metabolites, such as prostaglandins and leukotrienes [ 6 , 12 , 16 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that inflammation potently mediates the pathological process of PD. Activated macrophages produce a wide array of inflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor α, which stimulate the synthesis and release of PG, leading to excessive contraction of uterine smooth muscles and ischemic injury in PD [7,8]. As a core part of inflammation, the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome is involved in a wide array of acute and chronic diseases, such as coronary heart disease, stroke, pneumonia, acute kidney injury, and viral hepatitis [9].…”
Section: Introductionmentioning
confidence: 99%